Violence and social injustice against lesbian, gay and bisexual people - Sloan, Lacey M.; Gustavsson, Nora S. (New York: Harrington Park Press, 1998)
"Lacey M. Sloan; Nora S. Gustavsson Fonds Suzan Daniel (FSD) ook uitgegeven als Journal of Gay & Lesbian Social Services 08(1998) 3"